Optimal gating angles for a three-phase 60 Hz voltage source multi-level inverter based on intelligent algorithms - Hussein, Taha Ahmed; Ishak, Dahaman; Alkhateeb, Jawad Hasan; Salem, Mohamed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The three-phase multi-level inverter is considered one of the main power sources in industrial applications as well as in renewable energy applications. Therefore, researchers are interested in improving the efficiency of the inverter by reducing the total harmonic distortion (THD) value to its lowest limits. Also, one of the factors for improving the efficiency of the inverter is reducing the number of switches used, as it contributes to reducing the resulting losses. This research resorts to using many optimal algorithms to find the optimal values for the inverter gating angles that ensure reducing the THD value, as well as using a suitable topology with a least number of switches. The research used five algorithms known for their accuracy and efficiency, genetic algorithm (GA), gray wolf optimization (GWO), particle swarm optimization (PSO), slime mould algorithm (SMA), and whale optimization algorithm (WOA) separately. Then, extracting the distinctive characteristics of these algorithms in a hybrid curve and using it in driving the three-phase multi-level inverter (MLI) with 31 levels. The research displays the voltages and currents of the inverter as well as the frequency analysis for three-phase inductive load resulting from simulating the inverter using MATLAB software.